2010
DOI: 10.1136/thx.2010.139998
|View full text |Cite
|
Sign up to set email alerts
|

Unusual life-threatening Rosai-Dorfman disease of the trachea: role of NF- B

Abstract: RosaieDorfman disease (RDD) is a rare non-neoplastic histioproliferative disorder characterised by painless lymphadenopathy, low fever, high erythrocyte sedimentation rate, leucocytosis and hypergammaglobulinaemia. Overactivity of nuclear factor kB (NF-kB) is linked with inflammatory, cancerous and autoimmune diseases. The first case is described of an unusual life-threatening RDD of the trachea with no lymphadenopathy at risk of suffocation in a 39-year-old Chinese woman. A diagnosis of RDD was made following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Those are founded with accounting for 40% of RDD. On the other hand, intrathoracic manifestations of RDD are rare and represent only 2% of the cases with RDD (Foucar et al 1990), and only 9 cases of RDD with localized intrathoracic lesions have been reported (Table 1) (Ohori et al 2003;Shi et al 2009;Ali and Mackay 2009;Hida et al 2009;Zhou et al 2010;Roberts and Attanoos 2010;Cartin-Ceba et al 2010;Kaseda et al 2011). The discriminative pathological findings of the present patient were diffuse bronchial proliferation of histiocytes with round or oval shaped nuclei and clear and weakly acidophilic cytoplasm (McClain et al 2004).…”
Section: Clinical Reportmentioning
confidence: 86%
See 1 more Smart Citation
“…Those are founded with accounting for 40% of RDD. On the other hand, intrathoracic manifestations of RDD are rare and represent only 2% of the cases with RDD (Foucar et al 1990), and only 9 cases of RDD with localized intrathoracic lesions have been reported (Table 1) (Ohori et al 2003;Shi et al 2009;Ali and Mackay 2009;Hida et al 2009;Zhou et al 2010;Roberts and Attanoos 2010;Cartin-Ceba et al 2010;Kaseda et al 2011). The discriminative pathological findings of the present patient were diffuse bronchial proliferation of histiocytes with round or oval shaped nuclei and clear and weakly acidophilic cytoplasm (McClain et al 2004).…”
Section: Clinical Reportmentioning
confidence: 86%
“…It was reported that around 40% of RDD patients have lymph node disorders and extranodal involvement, but intrathoracic manifestations of RDD was reported in only 2% of patients with RDD (Foucar et al 1990). Furthermore, there have been only 9 cases of RDD with localized intrathoracic lesions (Ohori et al 2003;Shi et al 2009;Ali and Mackay 2009;Hida et al 2009;Zhou et al 2010;Roberts and Attanoos 2010;Cartin-Ceba et al 2010;Kaseda et al 2011). No standard treatment for RDD has yet been established, but a good prognosis has been reported (Foucar et al 1990), and another report (Gotou et al 2008) noted that 20% of the cases showed spontaneous remission.…”
mentioning
confidence: 99%
“…GA also has protective role on β 2 adrenergic receptor (β 2 AR) agonist‐stimulated receptor internalization and cell apoptosis . The combination of GA and β 2 AR led to a coordinate anti‐inflammatory function through the suppression of NF‐κB activation . GA also exhibited a glucocorticoid‐like inhibitory effect on inflammation without affecting the serum cortisol level .…”
Section: Discussionmentioning
confidence: 99%
“…Infiltration of the tracheobronchial tree may be responsible for an obstructive pattern on pulmonary function test. 22 On fiberoptic bronchoscopy, the size of tracheobronchial lesions ranged from granular infiltration to a 40 mm mass. Of note, subglottic stenosis can also be secondary to extrinsic compression by massive lymphadenopathy.…”
Section: Discussionmentioning
confidence: 99%